2020
DOI: 10.14283/jpad.2020.38
|View full text |Cite
|
Sign up to set email alerts
|

The Computerized Cognitive Composite (C3) in A4, an Alzheimer’s Disease Secondary Prevention Trial

Abstract: Background: Computerized cognitive assessments may improve Alzheimer’s disease (AD) secondary prevention trial efficiency and accuracy. However, they require validation against standard outcomes and relevant biomarkers. Objective: To assess the feasibility and validity of the tablet-based Computerized Cognitive Composite (C3). Design: Cross-sectional analysis of cognitive screening data from the A4 study (Anti-Amyloid in Asymptomatic AD). Setting: Multi-center international study. Participants: Clinically norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 27 publications
2
79
1
1
Order By: Relevance
“…In a large sample of older adults ( n = 4486), C3 performance was shown to be moderately correlated with cognitive performance on a composite of paper‐and‐pencil measures (PACC). 7 A smaller study similarly showed this correlation between the C3 and paper‐and‐pencil measures. 58 It also showed that the Cogstate C3 battery's memory tasks were best at identifying individuals’ subtle cognitive impairment, as defined by PACC performance.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…In a large sample of older adults ( n = 4486), C3 performance was shown to be moderately correlated with cognitive performance on a composite of paper‐and‐pencil measures (PACC). 7 A smaller study similarly showed this correlation between the C3 and paper‐and‐pencil measures. 58 It also showed that the Cogstate C3 battery's memory tasks were best at identifying individuals’ subtle cognitive impairment, as defined by PACC performance.…”
Section: Resultsmentioning
confidence: 77%
“…In clinically normal (CN) individuals, abnormal levels of Aβ (Aβ+), as measured in cerebrospinal fluid (CSF) (e.g., levels of Aβ 42 or Aβ 42/40 ) or with positron emission tomography (PET) neuroimaging, are considered indicative of an early AD pathological process. 2 , 3 During this preclinical stage of the disease continuum, the cross‐sectional association between Aβ and cognitive deficits is generally weak, 5 , 6 , 7 , 8 or insignificant. 9 , 10 , 11 However, CN individuals with higher Aβ burden (Aβ+) exhibit faster cognitive decline, 12 , 13 , 14 and often progress to a clinical stage faster than those with lower levels of Aβ.…”
Section: Introductionmentioning
confidence: 99%
“…Results from this 'Rate Of Change Sub-study' (AIBL-ROCS), confirmed that increased numbers of reassessments (i.e., > 8) improved sensitivity to A␤amyloid-related cognitive change in both preclinical and prodromal AD [63]. These data provided the foundation for the use of the CBB in other studies of AD genesis (e.g., the Mayo study of Health and Aging [64]) and in clinical trials designed to treat AD by clearing A␤-amyloid prior to the development of cognitive impairment (e.g., [65,66]).…”
Section: Cognitionmentioning
confidence: 91%
“…Development of the C3 included its use in the A4 study, a secondary prevention trial in clinically normal older adults with abnormal levels of amyloid who were randomized to receive placebo or solanezumab. This initial study showed that when the drug was administered in screening period, the amyloid-positive group performed worse on C3 compared to the Preclinical Alzheimer Cognitive Composite (PACC) ( 16 , 17 ). The C3 has also been shown to provide reliable data when participants complete the assessments at home on an iPad ( 18 ).…”
Section: Implementing Digital Devices In Ad Clinical Studiesmentioning
confidence: 99%